2000
DOI: 10.1007/s002530000443
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas aeruginosa rhamnolipids: biosynthesis and potential applications

Abstract: Pseudomonas aeruginosa produces and secretes rhamnose-containing glycolipid biosurfactants called rhamnolipids. This review describes rhamnolipid biosynthesis and potential industrial and environmental applications of rhamnolipids. Rhamnolipid production is dependent on central metabolic pathways, such as fatty acid synthesis and dTDP-activated sugars, as well as on enzymes participating in the production of the exopolysaccharide alginate. Synthesis of these surfactants is regulated by a very complex genetic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
266
3
12

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 497 publications
(290 citation statements)
references
References 0 publications
9
266
3
12
Order By: Relevance
“…Additionally, there are reports of vegetable oils depicting as more effective substrate in rhamnolipid production from P. aeruginosa compared to glucose, glycerol and hydrocarbons [15,[35][36][37]. However, in contrast to these findings Pseudomonas EMI strain used by Benincasa et al [14] showed that carbon sources such as glucose and glycerol were superior over the vegetable oils like olive and soya bean oil when tested with rhamnolipid yield and productivity.…”
Section: Rhamnolipid Productionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, there are reports of vegetable oils depicting as more effective substrate in rhamnolipid production from P. aeruginosa compared to glucose, glycerol and hydrocarbons [15,[35][36][37]. However, in contrast to these findings Pseudomonas EMI strain used by Benincasa et al [14] showed that carbon sources such as glucose and glycerol were superior over the vegetable oils like olive and soya bean oil when tested with rhamnolipid yield and productivity.…”
Section: Rhamnolipid Productionmentioning
confidence: 99%
“…There are certain reports that mark the type and concentration of carbon substrates which affect the production of rhamnolipid yield [18,35]. Wei et al…”
Section: Rhamnolipid Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to directly causing tissue destruction, elastase also protects P. aeruginosa during infection by degrading immunoglobulins and complement proteins (Bainbridge & Fick, 1989;Cripps et al, 1995). Another class of QS-controlled product that affects the immune system is rhamnolipids, bioactive molecules with surfactant properties, synthesized by RhlAB, with the most abundant being L-rhamnosyl-3-hydroxydecanoyl-3-hydroxydecanoate (rhamnolipid 1) and 2-O-a-L-rhamnopyranosyl-a-L-rhamnopyranosyl-b-hydroxydecanoyl-b-hydroxydecanoic acid (rhamnolipid 2, also referred to as rhamnolipid B by Jensen et al, 2007;Lang & Wullbrandt, 1999;Maier & Soberon-Chavez, 2000). Although rhamnolipids were initially proposed to play a role in maintaining void spaces between microcolonies or for biofilm dispersal in vitro, we have subsequently shown that PMNs are unable to eradicate bacterial cells within P. aeruginosa biofilms in vitro .…”
Section: Qs-regulated Virulence Factors Involved In Lung Infectionsmentioning
confidence: 99%
“…Biosurfactant production has traditionally been viewed as a mechanism to enhance hydrocarbon biodegradation by increasing the apparent aqueous solubility of the hydrocarbon [52][53][54][55][56][57][58][59][60][61] or by enhancing the interaction of the microbial cell with the hydrocarbon [60,62,63]. By dispersing or increasing the apparent solubility of poorly soluble hydrocarbons, especially polynuclear aromatic compounds, these compounds become more bioavailable and, thus, more amenable to biodegradation [57,61,[64][65][66].…”
Section: Biosurfactantsmentioning
confidence: 99%